2013
DOI: 10.1186/1475-2840-12-155
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical atherosclerosis and metabolic syndrome increase cardio- and cerebrovascular events rate: a 20-year follow up

Abstract: BackgroundIntima-media thickness (IMT) is a validated marker of preclinical atherosclerosis and a predictor of cardiovascular events.PatientsWe studied a population of 529 asymptomatic patients (age 62 ± 12.8 years), divided into two groups of subjects with and without Metabolic Syndrome (MetS).MethodsAll patients, at baseline, have had a carotid ultrasound evaluation and classified in two subgroups: the first one without atherosclerotic lesions and the second one with preclinical atherosclerosis (increased IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Hypertriglyceridemia, as one of the components of the MS, is closely related to a constellation of metabolic risk factors including a central distribution of adiposity or visceral obesity, insulin resistance, impaired glucose tolerance, hypertension, and high TG and/or low HDL-C, associated with an atherogenic, procoagulant, and proinflammatory state [56][57][58][59][60][61][62][63][64].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%
“…Hypertriglyceridemia, as one of the components of the MS, is closely related to a constellation of metabolic risk factors including a central distribution of adiposity or visceral obesity, insulin resistance, impaired glucose tolerance, hypertension, and high TG and/or low HDL-C, associated with an atherogenic, procoagulant, and proinflammatory state [56][57][58][59][60][61][62][63][64].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%
“…Relationship between metabolic syndrome and CVD Many studies have shown that patients with the metabolic syndrome have more prevalent and greater risk to develop CVD (59)(60)(61)(62)(63)(64)(65). In these studies, the increased CVD risk ranged from 30 to 400%; this wide variation is probably due to the population, the inclusion criteria, and the length of follow-up.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…In studies demonstrating that metabolic syndrome was associated with higher CVD risk (59)(60)(61)(62)(63)(64)(65)(66)(67), this excess risk remained after adjustment for other conventional risk factors. This would suggest that if other risk factors are included in the definition, the predictive value of the syndrome may improve.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…1,6,8,12 A prospective study published by Novo et al showed that in the subgroup of patients with MetS, the prevalence of subclinical atherosclerosis, defined as increased IMT (common carotid IMT > 0.90 mm) with or without atherosclerotic plaque, was significantly higher than in participants without MetS and defined this Syndrome as a CV risk factor: participants with MetS had a significantly higher prevalence of vascular disease in a 20-year follow-up (49%) than participants without MetS (29%) (p < 0.01). 9,13 Conversely, little is known about the predictive role of MetS in peripheral arterial disease (PAD), which affecting about 27 million people in Europe and the United States. Brevetti et al found that more than 50% of PA D patients met the criteria for rATP III-MetS.…”
Section: Metabolic Syndrome and Peripheral Arterial Disease Síndrome mentioning
confidence: 99%